Hydro-Mechanical Behaviour of a Rainfall-Induced Landslide by Instrumental Monitoring: Landslide-Rainfall Threshold of the Western Black Sea Bartin Region of Turkiye - Taskiran, Taha; Allı, Serdar; Yılmaz, Yüksel; Allı, Serdar (Mdpi, 2023)
Bartin City is located in the Western Black Sea Region of Turkiye, where rainfall-induced landslides are more frequently observed. Although it is known that many landslides are induced by rainfall, there is limited knowledge regarding how rainfall triggers these landslides in the city. To clarify the triggering mechanisms of rainfall-induced landslides, a detailed field monitoring program was performed on a chosen area to represent landslides in Bartin. The instrumentation included the measurements of site suction, volumetric water content, groundwater level, and rainfall amount over a period of two years. Various stability analyses were performed regarding pore pressures after both transient flow infiltration analysis and site-measured suction values. The rainfall intensity-duration thresholds were obtained for both dry and wet periods as a result of the numerical analyses performed by means of parameters obtained from field monitoring. The results show that the wet period conditions create more critical conditions before failure compared to the dry period conditions, so landslides occur more easily in wet periods. According to the landslide-rainfall threshold relations, landslide-risk limits are reached if the rainfall intensity is over 10 mm/h for the dry periods and lasts between 0.85 h and 17 h depending on the saturated hydraulic conductivity of the soil. When the rainfall intensities are less than 10 mm/h, longer rainfall durations are needed for a landslide to occur. For the wet periods, landslide-risk situations are encountered if the rainfall intensity over 1 mm/h continues for 0.36 h-3.67 h, depending on the saturated hydraulic conductivities.
Keywords: Landslide; Instrumental Monitoring; Rainfall Threshold; Matric Suction; Early Warning; Data Collection & Analysis